SARAWAK NON-FUNGIBLE TOKEN (NFT) MARKETPLACE - David, Bong Xia Shing (Universiti Malaysia Sarawak, (UNIMAS), 2023)
This project aims to develop an NFT marketplace for Sarawak, with a focus on the art industry. This report included a thorough analysis of user needs and requirements, as well as the design and implementation of the NFT Marketplace. The marketplace allows users to mint, sell, and buy NFTs, bringing potential evolution to the art industry in Sarawak. The project includes the design and development of a working prototype, which allows for minting, selling, and buying of NFTs. The project is developed using the combination of MEVN stack, Solidity, Hardhat and Ethereum blockchain. MEVN stack is a popular tech stack which consists of MongoDB, Express.js, Vue.js, and Node.js. The marketplace is expected to be a significant step towards the integration of NFT technology in the art industry in Sarawak and it is expected to be on par with the global NFT marketplaces. A comprehensive evaluation was conducted to test the proposed system. The result shows the system has passed all the functionality test, but there are still rooms for improvement on the system user experience